Proctor Application Benefits in Post Pandemic Online Test Implementation - Ervina C M Simatupang; Puspita Sari; Hero Gunawan (Jurnal Sinestesia, 2023)
Proctor applications have emerged as a safeguard for maintaining the integrity of online assessments. One of the foremost advantages is their ability to deter cheating and academic dishonesty. By employing features such as live video monitoring, screen recording, and AI-driven behavior analysis, these applications provide a comprehensive means to ensure that students' performances are genuine reflections of their knowledge and abilities. This not only upholds the credibility of the evaluation process but also instills a sense of fairness and equity among test-takers. The result of this research, proctor applications have effectively transcended the limitations of physical invigilation. A significant proportion of participants (approximately 55%) indicated that they perceived no substantial difference in the level of confidence between the two assessment approaches. Moreover, a majority of respondents (around 45 %) Geographical barriers are rendered inconsequential as students can undertake assessments from remote locations without compromising test security. This inclusivity expands educational opportunities, particularly for individuals who may have previously encountered difficulties in attending on-site examinations. The flexibility offered by proctor applications is another pivotal advantage. Institutions can conduct tests at different times, catering to diverse schedules and time zones. This flexibility not only accommodates students' varying circumstances but also minimizes technical glitches by alleviating the strain on servers during peak usage periods.